The Influence of Teachers' Professional Competence on Student Learning Outcomes in Social Science Education Subjects - Marlina Hernawati; Yorman; Hully; Ihsan; Irhas (International Journal of Social Sciences and Humanities, 2024)
This study aims to prove the influence of teacher professional competence on student learning outcomes at MTs Darul Hikmah Az-zikri NW Pringgarata and to examine how much teacher professional competence can illuminate student learning outcomes. This study uses a quantitative approach with the Associative method. Data were collected using questionnaires and documentation studies, where sampling applied a simple random sampling system distributed to 47 students. The questionnaire form applied a Likert scale score with four alternative answers, while the documentation study was only a complementary technique in data collection. Based on data processing and the results of SPSS ver.26 calculations, statistical testing resulted in Ho being rejected and Ha being accepted, which explained that there was an influence between teacher professional competence on student learning achievement. This was obtained from the results of the T-test which produced a significance value of 0.000 <5% (0.05). The calculation of the determination coefficient explains that the teacher professional competence variable is able to explain the student learning outcome variable by 25%. While the remaining 75% is explained by other variables that were not studied.